BACLOFEN, RACLOPRIDE, AND NALTREXONE DIFFERENTIALLY REDUCE SOLID FAT EMULSION INTAKE UNDER LIMITED ACCESS CONDITIONS - RE, Rao (2008)
Previous work in rats has demonstrated that an Intermittent (Monday, Wednesday, Friday) schedule of access promotes binge-type consumption of 100% vegetable shortening during a 1-hour period of availability. The present study used novel shortening-derived stable solid emulsions of various fat concentrations. These emulsions were the consistency of pudding and did not demonstrate oil and water phase separation previously reported with oil-based liquid emulsions. Male Sprague-Dawley rats were grouped according to schedule of access (Daily or Intermittent) to one of three concentrations (18%, 32%, 56%) of solid fat emulsion. There were no significant Intermittent vs. Daily differences in amount consumed, due to high intakes in all groups. This indicated the acceptability of the emulsions. Baclofen (GABA-B agonist) and raclopride (D2-like antagonist) both significantly reduced emulsion intake in all Daily groups, but only in the 56% fat Intermittent group. Naltrexone (opioid antagonist), in contrast, significantly reduced 32% and 56% fat emulsion intake in the Intermittent, as well as the Daily groups. These results indicate that the fat intake reducing effects of GABA(B) activation and D2 blockade depend upon fat concentration and schedule of fat access, while the fat intake reducing effects of opioid blockade depend upon fat concentration but not schedule of access.